Alternating Rabacfosadine/Doxorubicin: Efficacy and Tolerability in Naïve Canine Multicentric Lymphoma. (3rd April 2017) - Thamm, D.H.; Vail, D.M.; Post, G.S.; Fan, T.M.; Phillips, B.S.; Axiak‐Bechtel, S.; Elmslie, R.S.; Klein, M.K.; Ruslander, D.A.
Abstract : Background: Standard of care treatment for multicentric lymphoma in dogs remains doxorubicin (DOX)‐based combination chemotherapy, but owners may hesitate to commit the time and financial resources to complete such a protocol, typically requiring 12–16 visits. Rabacfosadine (RAB), a double prodrug of the nucleotide analog 9‐(2‐phosphonylmethoxyethyl) guanine, has substantial single‐agent activity in dogs with lymphoma, and a different mechanism of action than DOX. Hypothesis/Objectives: Our objective was to evaluate the efficacy and adverse effect (AE) profile of alternating doses of RAB and DOX in dogs with naïve multicentric lymphoma. Animals: Fifty‐four dogs with previously untreated lymphoma. Methods: Open‐label, multicenter prospective clinical trial. Dogs received alternating RAB (1.0 mg/kg IV weeks 0, 6, 12) and DOX (30 mg/m 2 IV weeks 3, 9, 15). Dogs that achieved complete response (CR) were followed by monthly evaluations. Complete clinicopathological evaluation and assessment of remission and AEs were performed every 21 days. Results: The overall response rate was 84% (68%; CR; 16%; partial response [PR)]. The overall median progression‐free interval (PFI) was 194 days (216 for CR and 63 for PR). Most AEs were mild and self‐limiting: gastrointestinal and hematologic AEs were most common. Thirteen dogs experienced dermatologic AEs, and 2 dogs developed grade 5 pulmonary fibrosis. Conclusions and Clinical Importance: Alternating RAB/DOX generally was well tolerated and resulted in PFIs comparable to standard DOX‐based multi‐agent protocols, with fewer treatment visits. Most adverse events were mild or moderate and self‐limiting. Further studies are warranted to explore long‐term outcome and other RAB chemotherapy combinations.